El desarrollo como frontera de la conservación:: Reflexiones hacia un tipo de conservación colaborativa en áreas naturales protegidas - Cabral, Victoria N. (2019)
The article´s starting point is a project of territorial intervention in the Biosphere Reserve Parque Atlántico Mar Chiquito. The aim of the project was to mitigate the impact of debris in coastal zones. During its execution, a clash of interests between distinct local residents (i.e., neighbors, recreational fishermen and fishing operators) with distinct positions in regard to the development of the reserve were evidenced. Given that it is a reserve of multiple uses, in many cases predominates a utilitarian vision, in which conservation is considered an incompatible element with development. Taking this into consideration, the objective of this article is to analyze the visions of local actors about development and conservation. The methodological strategy consists in carrying out in-depth interviews with neighbors, recreational fishermen and fishing operators. From this, an optimal type of conservation for the reserve is proposed, which serves as a reference for others with similar characteristics.